Enhancing AES algorithm with arithmetic coding - Mukesh, Patel Sanket; Pandya, Morli S.; Pathak, Shreyas (2013 International Conference on Green Computing, Communication and Conservation of Energy (ICGCE), 2013)
Arithmetic coding technique is very much effective and flexible and it is evident in most of the circumstances while on the other hand AES is advanced encryption standard process which deals with changeover and permutation of data for proper security. The paper presents the security and compression of data by Arithmetic coding with AES (Advanced Encryption Standard) algorithm. Basic research is to arithmetically encode the data first, followed by encryption by using AES algorithm and then transmits the code. At the receiving end the data is decrypted and decoded to produce the user data. The paper has an advantage of encoding/decoding and compression of data both at the same time. The input data size is of 128 bits or 256 bits in AES, so the idea is to compress the data before encryption by digital arithmetic coding. The arithmetic coding and Huffman coding are very much alike in their working as they both achieve the task of compression by plummeting the average number of bits required to represent each and every symbol.